Facilitative coaching: a guide for youth sport leaders. Issue 2 (3rd April 2018) - Newman, Tarkington J.; Kim, Melissa; Alvarez, M. Antonio G.; Tucker, Anita R.
ABSTRACT: When utilizing youth sport as a social intervention to promote positive youth development (PYD) outcomes, the programming and practices of the youth sport leader (YSL) are critical. However, many YSLs lack the education and knowledge to effectively facilitate sport towards desired PYD outcomes such as intrapersonal and interpersonal life skill development and the transfer of learning. One model designed to help guide the intentional programming and facilitative coaching practices of YSLs is  the Coaching on the Wave (CotW) model. However, the current version of the CotW model lacks a clear pedagogical approach with explicit practices, strategies and techniques that would allow practitioners to fully access its benefits. To further enhance the CotW model, the current paper proposes the integration of key adventure pedagogy tenets into a revised and adapted model. Through the use of the updated CotW model, YSLs will be better equipped to develop facilitative coaching practices to intentionally facilitate sport towards PYD.